Inter-cultural and inter-ethnic dialogue as a condition and guarantee of stable development - Shermuhamedova, . (Opción, 2019)
The aim of the study is to investigate inter-cultural and inter-ethnic dialogue as a condition and guarantee of stable development via qualitative comparative research method. As a result, the processes of formation of global culture, occurring in modern society and the simultaneous strengthening of the value of ethno-cultural identity have a great influence on libraries. In conclusion, only due to the mutual understanding of different nations and nationalities, mankind will be able to avoid distrust, which is used as a basis for inciting hostility, hatred, and calls for violenc